Pulsed Neural Network Cell in Integrated Circuit - Paukštaitis, V.; Dosinas, A. (Elektronika ir Elektrotechnika, 2010)
The research of the created model of artificial pulsed neuron is presented. The peculiarities of building semiconductor integrated circuit with neuron cell and the artificial neural network constructed from such cells are discussed. The principle of operation of the artificial pulsed neural cell and the compensation methods of parameter variation due to temperature are unclosed for the reader. The model and the test bench of the artificial pulsed neuron cell are implemented in semiconductor factory calibrated design-kit. The obtained simulation results corroborated the research results of the earlier formed information streams model and showed that the designed artificial pulsed neuron cell is viable in the wide temperature range. The paper also presents the research of other electrical characteristics of the artificial pulsed neuron. The conceptual layout is presented and the synthesis aspects of the pulsed artificial networks are discussed. Ill. 7, bibl. 6 (in English; summaries in English, Russian and Lithuanian).